The Cross and the Wheel: An Introductory Study of the Merging of Eastern Religions and Christianity in T.S. Eliot?s Four Quartets - Saravia Vargas, Juan Carlos (Escuela de Lenguas Modernas, Universidad de Costa Rica, 2011)
.